International Monetary Fund Annual Report 2021 Financial Statements. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 2021)
The audited financial statements that follow form Appendix VI of the International Monetary Fund's Annual Report 2021 and can be found, together with Appendixes I through V and other materials, on the Annual Report 2021 web page (www.imf.org/AR2021). They have been reproduced separately here as a convenience for readers. Quarterly updates of the IMF's Finances are available at www.imf.org/external/pubs/ft/quart/index.htm.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Public Administration